Review: Making sense of Bad English - Padilla, Alexander (Kronos – The Language Teaching Journal, 2021)
To recognize what is or what is not the good use of English, language scientist have disposed the official term “Standard English”. If so, what does this term really means? and what were the conditions and bounds where this term was created? and in consequence, who are the people that really speak on this strict way? This book discusses through an anthropological and linguistic way the term “Good English”. Thus, in general words the author will discuss: How can somebody know whether his use of English is good or bad? What are the causes of such distinction (good/bad) in real practices using this language? Moreover, the specific objective beyond the common negative answer about the not standardized English, this book will offer an explanation from the social, cultural and historical facts about the meaning of being an English user in different parts of the world.